Postoperative Bowel Perforation due to Heterotopic Ossification (Myositis Ossificans Traumatica): A Case Report and Review of the Literature - Victoria Valinluck Lao; Oliver B. Lao; Edgar Figueredo (Case Reports in Gastrointestinal Medicine)
Heterotopic ossification (HO) is the ectopic development of normal bone within soft tissue that can occur after traumatic injury. It is uncommon and may be missed or misdiagnosed, which can lead to complications. We report the case of an 84-year-old male with a previous history of a laparotomy who underwent resection of an intra-abdominal tumor through a midline incision. On postoperative day six, the patient was taken to the operating room, as succus was draining from the incision. Upon re-exploration, sharp bone-like material was found in the wound directly adjacent to an enterotomy. Pathology confirmed mature lamellar bone and the diagnosis of HO. This is the first report of postoperative intestinal perforation secondary to HO in a midline wound. We report this case to encourage accurate reporting of HO and its morbidity and complications for the benefit of appropriate surgical planning and epidemiologic tracking of outcomes.